"You hear my funny accent?!": problematizing assumptions about Afro-Caribbean "teachers turned educators". Issue 3 (2nd July 2020) - Smith, Patriann; Warrican, S. Joel; Alleyne, Melissa L.
ABSTRACT: Increasingly, teacher educators are required to prepare teachers for students in mainstream classrooms who are more culturally and linguistically diverse than ever before. Yet, calls for teacher educators to model enactments of curriculum and instruction concerning diversity expected of prospective teachers in U.S. K-12 classrooms have resulted in few efforts that attempt to understand and to document the personal predispositions, attitudes, beliefs, and experiences of culturally and linguistically diverse teacher educators. This study examines the learning of five vernacular-speaking Afro-Caribbean "teachers turned educators" (TTEs) about their multilingual and multicultural awareness after they migrated across cultures from their home countries to the United States. Findings indicated that the TTEs demonstrated learning about their awareness by modifying their intonation, message content, facial expressions, deciding to speak or to be silent, and identifying previously overlooked concerns about language in their home countries. Reflexivity was critical to learning about their multilingual awareness and specific sources for navigating cultural incongruence were useful for learning about their multicultural awareness. The TTEs developed " transnational linguistic fluidity" in their demonstration of awareness through learning, raising questions about the inadvertent assumption that immigrant, multilingual, and Black educators naturally reflect an awareness of language and culture.